In vivo protein crystallization in combination with highly brilliant radiation sources offers novel opportunities for the structural analysis of post‐translationally modified eukaryotic proteins. Issue 8 (1st August 2015) - Duszenko, Michael; Redecke, Lars; Mudogo, Celestin Nzanzu; Sommer, Benjamin Philip; Mogk, Stefan; Oberthuer, Dominik; Betzel, Christian
<x xml:space="preserve">Abstract</x> During the last decade, the number of three‐dimensional structures solved by X‐ray crystallography has increased dramatically. By 2014, it had crossed the landmark of 100 000 biomolecular structures deposited in the Protein Data Bank. This tremendous increase in successfully crystallized proteins is primarily owing to improvements in cloning strategies, the automation of the crystallization process and new innovative approaches to monitor crystallization. However, these improvements are mainly restricted to soluble proteins, while the crystallization and structural analysis of membrane proteins or proteins that undergo major post‐translational modifications remains challenging. In addition, the need for relatively large crystals for conventional X‐ray crystallography usually prevents the analysis of dynamic processes within cells. Thus, the advent of high‐brilliance synchrotron and X‐ray free‐electron laser (XFEL) sources and the establishment of serial crystallography (SFX) have opened new avenues in structural analysis using crystals that were formerly unusable. The successful structure elucidation of cathepsin B, accomplished by the use of microcrystals obtained by in vivo crystallization in baculovirus‐infected Sf9 insect cells, clearly proved that crystals grown intracellularly are very well suited for X‐ray analysis. Here, methods by which in vivo crystals can be obtained, isolated and used for structural analysis by novel highly brilliant XFEL and synchrotron‐radiation sources are summarized and discussed.